Lipid Panel Predictors Of Decubitus Ulcer Risk In Elderly Residents Of Bina Bhakti Nursing Home - Singh, Arwinder; Santoso, Alexander Halim; Teguh, Stanislas Kotska Marvel Mayello; Satyo, Yovian Timothy; Tan, Nikita (Lembaga Pengembangan Kinerja Dosen, 2025)
Decubitus ulcers in the elderly arise from prolonged pressure, reduced mobility, and skin compromise, increasing morbidity and costs. Risk assessment includes clinical tools like the Braden Scale and biochemical markers such as lipid profiles and apolipoproteins. Age-related vascular and skin changes, along with lipid imbalances, further influence ulcer risk. To evaluate the relationship between lipid panel components and the risk of decubitus ulcers in elderly residents at Bina Bhakti Nursing Home using the Braden Scale. A cross-sectional analytic study included 93 elderly participants aged over 60 years. Lipid profiles were measured via enzymatic and immunoturbidimetric assays, including HDL, LDL, triglycerides, total cholesterol, ApoA, and ApoB, alongside their ratios. The Braden Scale was employed to assess ulcer risk. Non-parametric Spearman correlation and multiple regression analyses were conducted using SPSS version 26 to identify significant predictors, with statistical significance set at p<0.05. Significant positive correlations were found between decubitus ulcer risk and ApoA (p=0.024), ApoB (p=0.023), total cholesterol (p=0.033), and LDL (p=0.013). Conversely, age showed a significant negative correlation (p=0.027). Lipid ratios, including ApoB/ApoA and triglyceride/HDL, did not demonstrate statistical significance. Multiple regression highlighted ApoB, ApoB/ApoA ratio, and LDL/ApoA ratio as independent predictors, emphasizing their role in vascular health and tissue integrity. Elevated ApoB and unfavorable lipid ratios are key predictors of increased decubitus ulcer risk, likely due to their contribution to endothelial dysfunction and impaired circulation. Addressing lipid imbalances through targeted interventions could enhance tissue health and reduce ulcer susceptibility in the elderly population.